French penetration in Mount Lebanon In the nineteenth century (Journal of the College of Basic Education, 2022)
The issue of French penetration into Mount Lebanon during the nineteenth century is considered one of the important topics that deserves study, as it is looking at a region that has long been clamored for by colonial countries, especially France, which took many means to penetrate that region, the most important of which is the religious, economic and then political aspects. France found fertile ground in its entry into Mount Lebanon. Lebanon, as the Maronite community facilitated many difficulties for it, since both sides are Catholic Christians, and the Maronites found themselves in the arms of France and its kings as a result of the protection they provided to the Maronite community.